Tips, Tricks, and Guides in Descemet Membrane Endothelial Keratoplasty Learning Curve - Davide Borroni; Carlos Rocha de Lossada; Mohit Parekh; Kunal Gadhvi; Chiara Bonzano; Vito Romano; Hannah J. Levis; Aris Tzamalis; Bernhard Steger; Miguel Rechichi; Marina Rodriguez-Calvo-de-Mora (Journal of Ophthalmology)
Lamellar keratoplasty is fast becoming the most popular form of corneal transplantation. The adoption of Descemet membrane endothelial keratoplasty (DMEK) in the management of Fuchs endothelial dystrophy and pseudophakic bullous keratopathy is partly responsible for this shift in the paradigm of management of corneal pathology. The learning curve of DMEK, however, has been proven to be much steeper than previous endothelial keratoplasty procedures. To ease the procedure, experts have proposed multiple innovative techniques from tissue preparation to graft unfolding to aid the more novice surgeon. Here, we collate and share tips and tricks from our collective experiences to support the learning curve and outcomes in DMEK for both the novice and more experienced corneal transplant surgeons.